Characterization of Salmonella species from water bodies in Dar-Es-Salaam city, Tanzania - Kweka, Eliningaya (Journal of Health & Biological Sciences, 2013)
Background: Water-borne diseases are the most common cause of illness and death among the poor population from developing countries. The majority of the people are inadequately aware that aquatic environment is a major source of salmonellosis. Dar es Salaam city is among the cities with most of its population live in squatter. Typhoid fever ranks second with 14.3% of all notifiable disease cases in the city. The city experience water scarcity which forces water wells and rivers to become the main sources of water for domestic use and livestock. This study therefore, characterized Salmonella strains from different water bodies of city as possible sources for enteric diseases endemicity. Methods: The Salmonella Chromogenic Agar (SC Agar) and Kligler Iron Agar (KIA) media were used for isolation and enumeration of the strains. The inoculated cultures were incubated at 370C for 24 hours. Salmonella colonies were confirmed by magenta colorations and hydrogen sulfide production on SC Agar and KIA Agar, respectively. The Analytical Profile Index 20 Enterobacteriaceae kit (API 20E kit) was used to identify Salmonella species. Results: Based on the API 20E kit, the identified Salmonella species from different water bodies were Salmonella ser. paratyphi A (96.9%), Salmonella cholelaesuis spp choleraesuis (99.5%) and Salmonella typhi (99.9%). Conclusion: This study shows that shallow wells and rivers which are mainly used by the city dwellers were highly contaminated with Salmonella and were more contaminated than deep wells and marine water bodies. This warrants further investigation on the disease mapping in the urban and peri-urban areas.